The strategy of improving convergence of genetic algorithm - Jiang Jing; Meng Lidong (Institute of Advanced Engineering and Science, 2012)
Premature convergence is the main obstacle to the application of genetic algorithm. The study on convergence of GA is always one of the most important theoretical issues. Via analyzing the convergence rate of GA, the average computational complexity can be implied and the optimization efficiency of GA can be judged. This paper proposed an approach to calculating the first expected hitting time and analyzed the bounds of the first hitting time of concrete GA using the proposed approach. And this paper proposed a strategy which included transformation of fitness function, self-adaptive crossover and mutation probability and close relative breeding avoidance method in order to overcome premature convergence. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1641